Organic redox cascade cyclization of 2-alkynylquinones by ascorbic acid in combination with a copper catalyst and its application to formal synthesis of liphagal. (24th January 2023) - Jeong, Taejoo; Okanishi, Yusuke; Yotsui, Sora; Kim, In Su; Yoshimitsu, Takehiko
Abstract : The combination of a quinone-ascorbic acid organic redox reaction and a concomitant copper catalysis in situ enables new approach to hydroxybenzofurans with structural variations. Abstract : A stoichiometric amount of ascorbic acid in combination with CuCl2 ·2H2 O catalyst was found to promote the organic redox cascade transformation of alkynylquinones, successfully furnishing hydroxybenzofuran derivatives. By applying the present organic redox-driven copper-catalyzed cyclization protocol, a formal synthetic route to liphagal has been developed.